Medidas de solubilidade de corantes têxteis com líquidos iônicos próticos com base catiônica metil monoetanolamina - Croscato, Gilson dos Santos (2018)
The high consumption of water in the textile industry, which is estimated for each kilogram of textile processed, a consumption between 100 to 150 liters of water, reinforces the need for alternative processes. The technology of ionic liquids (ILs) the object of this study, is a recent advance and it stands out in replacement of organic solvents in a variety of areas with good prospects for short-term implementation. Within this context, the present work aimed the synthesis of ionic liquids protics (ILPs), from the base cation methyl monoethanolamine in addition to solutions ranging from the anionic alkyl chain of the acetic acid, propionic acid, butyric acid and pentanoico, as well as the measure of solubility data of textile dyes of different classes (acid, disperse and reactive) in ILPs synthesized. The identification of the compounds was demonstrated through the technique of Nuclear Magnetic Resonance (NMR). It was determined the water content, the density, the viscosity, the thermogravimetry (TGC/DSC) and the conductivity for the ILP synthesized. The results have verified similarity with the data reported in the literature. In the determination of solubility was made out an experimental apparatus with heating and mechanical agitation providing a homogeneity in the saturated mixture between the ILP and the dye. The determination of solubility was performed in UV-VIS spectrophotometer, using calibration data obtained from solutions with different concentrations of the dyes in study in base of cation methyl monoethanolamine. The water content has interfered in the values obtained through the acid and reactive dyes, which has water solubilising groups in their chemical structure, which does not occur for the dispersed dye. The increase in the group alkyl in the anion has not influenced the solubility of the dyes. The results gotten are promising for the application of the ILP as solvent in processes of dyeing textiles.